Semantics Application Networking for EFL learners' Communicative Language Learning - Buhari, Buhari (Journal of English Education and Teaching, 2023)
This study compares and contrasts the speaking activities that are regularly assigned to students in the classroom and explores how both teachers and students view the program's overall worth. The research uses experimental design as its methodology. Students who were enrolled in the first semester of the academic year 2021–2022 made up the study's population. The purposive sampling strategy was used by the current researcher. The researcher participated in two courses with a combined total of 80 students as samples for this study. The outcomes of this study are anticipated to provide important data and make a substantial addition to linguistic research, particularly in the field of language instruction. This study's sole objective was to use Semantics Networking Techniques to improve the students' oral English skills. The findings of this study highlight the significance of communicative language, language learning approaches, and semantic networking strategies in fostering students' development in various fields.